Deep versus moderate neuromuscular block during one-lung ventilation in lung resection surgery - Casanova,Javier (2017)
Abstract Background and objectives: Neuromuscular relaxants are essential during general anesthesia for several procedures. Classical anesthesiology literature indicates that the use of neuromuscular blockade in thoracic surgery may be deleterious in patients in lateral decubitus position in one-lung ventilation. The primary objective of our study was to compare respiratory function according to the degree of patient neuromuscular relaxation. Secondary, we wanted to check that neuromuscular blockade during one-lung ventilation is not deleterious. Methods: A prospective, longitudinal observational study was made in which each patient served as both treated subject and control. 76 consecutive patients programmed for lung resection surgery in Gregorio Marañon Hospital along 2013 who required one-lung ventilation in lateral decubitus were included. Ventilator data, hemodynamic parameters were registered in different moments according to train-of-four response (intense, deep and moderate blockade) during one-lung ventilation. Results: Peak, plateau and mean pressures were significantly lower during the intense and deep blockade. Besides compliance and peripheral oxygen saturation were significantly higher in that moments. Heart rate was significantly higher during deep blockade. No mechanical ventilation parameters were modified during measurements. Conclusions: Deep neuromuscular blockade attenuates the poor lung mechanics observed during one-lung ventilation.